Mindful Emotion Awareness Facilitates Engagement with Exposure Therapy: An Idiographic Exploration Using Single Case Experimental Design. Issue 1 (January 2022) - Curreri, Andrew J.; Farchione, Todd J.; Sauer-Zavala, Shannon; Barlow, David H.
Exposure therapy works through inhibitory learning, whereby patients are exposed to stimuli that elicit anxiety in order to establish safety associations. Mindful emotion awareness, or nonjudgmental and present-focused attention toward emotions, may facilitate engagement in exposures, which may in turn enhance therapeutic outcome. This study utilizes a single-case experimental design ( n = 6) to investigate the effect of mindful emotion awareness training on the use of avoidant strategies during exposures, distress during exposures, overall mindfulness, experiential avoidance, and symptom reduction in a sample of participants with social anxiety disorder. Data were analyzed using a combination of visual inspection and quantitative effect size metrics commonly applied in single-case experimental designs. To further investigate the relationship between distress and avoidant strategy use, contemporaneous and cross-lagged correlations were run. Results highlight individual differences in responses to mindful emotion awareness training and exposure exercises. Given these individual differences, repeated assessment and monitoring over the course of treatment may help clinicians most effectively identify treatment skills that will be most helpful for individual patients.